Observation of anti-parity-time-symmetry, phase transitions and exceptional points in an optical fibre - Arik Bergman (Nature Portfolio, 2021)
Exceptional points enable exotic optical responses, but they usually require complex devices. Here, the authors realise an anti-PT symmetric response supporting exceptional points through Brillouin interactions in a standard optical fibre, which can be tuned by simply controlling pump power and frequency.